Fabrication and Characterization of Bio-Nanocomposites Based on Halloysite-Encapsulating Grapefruit Seed Oil in a Pectin Matrix as a Novel Bio-Coating for Strawberry Protection - Gianluca Viscusi; Elena Lamberti; Francesca D’Amico; Loredana Tammaro; Giuliana Gorrasi (Nanomaterials, 2022)
In the framework of designing a novel bio-coating for the preservation of fresh fruits, this paper reports the design, preparation, and characterization of novel bio-nanocomposites based on pectin loaded with grapefruit seed oil (GO), a natural compound with antimicrobial properties, encapsulated into halloysite nanotubes (HNTs). The vacuum-based methodology was used for the encapsulation of the oil into the hollow area of the nanotubes, obtaining nano-hybrids (HNT-GO) with oil concentrations equal to 20, 30, and 50 wt%. Physical properties (thermal, mechanical, barrier, optical) were analyzed. Thermal properties were not significantly (p < 0.05) affected by the filler, while an improvement in mechanical performance (increase in elastic modulus, stress at breaking, and deformation at breaking up to 200%, 48%, and 39%, respectively, compared to pure pectin film) and barrier properties (increase in water permeability up to 480% with respect to pure pectin film) was observed. A slight increase in opacity was detected without significantly compromising the transparency of the films. The release of linoleic acid, the main component of GO, was followed for 21 days and was correlated with the amount of the hybrid filler, demonstrating the possibility of tailoring the release kinetic of active molecules. In order to evaluate the effectiveness of the prepared bio-composites as an active coating, fresh strawberries were coated and compared to uncoated fruit. Qualitative results showed that the fabricated novel bio-coating efficiently extended the preservation of fresh fruit.